Current Status of Knowledge and Preventive Practices among Hepatitis C patients in Twin Cities of Pakistan - Naeem Asim, Khuda Bux, Anwar Ali Malik, Zaka Un Nisa, Manthar Ali Mallah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the knowledge and preventive practice adopted by hepatitis C patients and the impact of hepatic C infection on their lifestyle. Methods: A cross-sectional survey was conducted in hepatic wards of tertiary care hospitals of Islamabad and Rawalpindi. A validated and reliable questionnaire was used comprised of 23 questions was administered to 370 patients admitted in the hepatic ward in tertiary care hospitals. For qualitative variables, frequencies and percentages were calculated. The inferential results were obtained using the Chi-square test. All analyses were performed using SPSS version 25.0 (IBM Corporation, Armonk, New York, USA). Statistical significance was defined as a two-tailed p value < 0.05. Results: Among 370 respondents, 350 responded to the questionnaire providing a response rate of 94.6%. The majority of the respondents, 306 (87.4%), were practicing infection control practices while 44 (12.6%) were not practicing the infection control practices. A significant association was seen between patients’ age, education, sex, and preventive practice. Among respondents, 162 (46.3%) had poor knowledge of the HCV infection, while 188 (53.7%) had good knowledge about Hepatitis C. Moreover, the study also reveals that knowledge of Hepatitis C has a significant relationship with preventive practices. Conclusions: In conclusions, most of the respondents showed a high level of hepatitis C knowledge and practiced infection control practices. It is also determined from this study that Hepatitis C negatively impacted the psychological status of patients.